Frequency of perineal lacerations and episiotomy in a university hospital in the mountain region of Rio de Janeiro (Research, Society and Development, 2020)
Perineal laceration is the most common complication in childbirth, occurring in 85% of vaginal deliveries and, to avoid it, episiotomy has been a routine procedure for a long time. However, episiotomy has been discouraged due to lack of proof of its benefit and its association with several complications. The aim of this study was to analyze the frequency of perineal lacerations and the performance of episiotomy in a university hospital in the mountain region in Rio de Janeiro, Brazil. Medical records of pregnant women whose vaginal delivery was performed between December 2018 and March 2019 were included in the study. Data on the presence of perineal lesions, including their degree, location, need for raffia, episiotomy and weight of the newborn were collected. The hospital's statistical sector provided data on episiotomy in the past 10 years and a trend curve was drawn. Pearson's chi-square test was applied. 137 medical records of pregnant women aged 19-38 years were eligible. A frequency of 56.9% perineal lacerations was observed, with 2.5% of serius injuries, need for raffia in 78.2% of cases and 22.6% of episiotomy procedures, mainly due to the narrow perineum and not complacent. The weight of the newborns varied between 875g to 3890g and most were classified as normal weight (n = 119, 87.5%). High frequency of perineal lacerations, mainly of mild severity, was found, as well as high frequency of episiotomy. However, data show a reduction of this procedure in the last ten years.